(untitled) (Proceedings of the International Conference on Education, 2021)
Entrance examinations for postgraduate students are used by institutions to value their capacity to perform during their studies and excel in professional practice. The medical field leverages this practice for postgraduate students to select the best candidates to enter a rigorous program where participants are responsible for patients outcomes. Therefore it is important to analyze the quality and predictability of those examinations. The objective of this study was to analyze the predictability of the medical residency entrance examination for academic performance. As part of the analysis, we correlated the academic performance of the 2018 generation of graduates in thirteen medical specialties at Tecnologico de Monterrey, with 64 students’ test scores. Academic performance was divided into students who graduated with honors and excellence (scores ≥90) and without honors. The admission test score has an 800-points total and was classified as high (≥600) and standard(≥550). The results show that from the participants, 37 had high entrance scores, of those 92% graduated with honors and excellence, and from the other 27 graduates which had a standard entrance score, 78% graduated with honors and excellence. The predictive positive value was 92% and the negative predictive value was 22%, whereas sensibility and specificity were calculated as 62% and 66%, respectively. Tecnologico de Monterrey’s admission test had a predictive value in medical specialties academic performance whereas not in negative predictive value, which could evidentiate that the formation in the academic program itself contributed to students’ professional and personal development. Factors like this might affect the sensibility and specificity values, further students would integrate more elements of performance scores to have added specificity and sensibility to assess and document performance